A Practical Approach to N-(Trifluoroacetyl)sulfilimines - Gries, Jörg; Krüger, Jochen (Synlett, 2014)
A new, simple method for the synthesis of N-(trifluoroacetyl)-protected sulfilimines from sulfides by a transition-metal-free, one-pot protocol is presented. The salient features of this process include the use of low-cost 1,3-dibromo-5,5-dimethylhydantoin, mild reaction conditions, and a broad substrate scope. The safety and robustness of the method has also been demonstrated by operations on a kilogram scale. In addition, a chiral resolution of a corresponding sulfoximine was achieved on a large scale.
Keywords: N-(trifluoroacetyl)sulfilimines; sulfilimines; sulfoximines; chiral resolution